External quality assessment of the molecular diagnostics and genotyping of meticillin-resistant Staphylococcus aureus - te Witt, R. (Springer-Verlag, 2010)
Two multicentre external quality assessments (EQA) for the molecular detection and genotyping of meticillin-resistant Staphylococcus aureus (MRSA) were arranged. Firstly, 11 samples containing various amounts of inactivated MRSA strains, meticillin-susceptible S. aureus (MSSA), meticillin-resistant coagulase-negative staphylococci (MRCoNS) or Escherichia coli were distributed to 82 laboratories. Samples containing 10(2) or 10(3) MRSA cells were correctly scored in only 16 and 46% of the datasets returned, respectively. Two of the used MSSA strains contained an SCCmec cassette lacking the mecA gene. There was a marked difference in the percentage of correct results for these two MSSA strains (37 and 39%) compared to the MSSA strain lacking the SCCmec cassette (88%). Secondly, a panel for MRSA genotyping, consisting of ten samples (two identical, three genetically related and five unique strains) was distributed to 19 laboratories. Seventy-three percent of the datasets recorded all samples correctly. Most pulsed-field gel electrophoresis (PFGE) protocols proved to be suboptimal, resulting in inferior resolution in the higher or lower fragment regions. The performance of molecular diagnostics for MRSA shows no significant changes since our first EQA in 2006. The first molecular typing results are encouraging. Both assessments indicate that programme expansion is required and that major performance discrepancies continue to exist.